2016
DOI: 10.5966/sctm.2015-0424
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Cell-Derived Sensory Neurons for Fate Commitment of Bone Marrow-Derived Schwann Cells: Implications for Remyelination Therapy

Abstract: Strategies that exploit induced pluripotent stem cells (iPSCs) to derive neurons have relied on cocktails of cytokines and growth factors to bias cell‐signaling events in the course of fate choice. These are often costly and inefficient, involving multiple steps. In this study, we took an alternative approach and selected 5 small‐molecule inhibitors of key signaling pathways in an 8‐day program to induce differentiation of human iPSCs into sensory neurons, reaching ≥80% yield in terms of marker proteins. Conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 53 publications
(67 reference statements)
1
30
0
Order By: Relevance
“…We have previously shown that forskolin, [D-Ala 2 ]-GIP, and exenatide protect frataxin-deficient β cells and neurons from apoptosis by decreasing oxidative stress (13,17). Recent developments in iPSC differentiation make it possible to generate functional sensory neurons using a 1-step protocol (46). We implemented this technology to differentiate sensory neurons from FRDA patients' iPSCs FA135 and HEL135 and also used 2 previously characterized control iPSCs, HEL115.6 and HEL46.11 (47,48).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that forskolin, [D-Ala 2 ]-GIP, and exenatide protect frataxin-deficient β cells and neurons from apoptosis by decreasing oxidative stress (13,17). Recent developments in iPSC differentiation make it possible to generate functional sensory neurons using a 1-step protocol (46). We implemented this technology to differentiate sensory neurons from FRDA patients' iPSCs FA135 and HEL135 and also used 2 previously characterized control iPSCs, HEL115.6 and HEL46.11 (47,48).…”
Section: Resultsmentioning
confidence: 99%
“…Two previously characterized FRDA iPSC lines (FA135, FA141, 2 clones of each) (43), 1 newly reprogrammed FRDA iPSC line (HEL135.2), and 2 previously characterized control iPSC lines (HEL46.11 and HEL115.6) (47, 48) were used for neuronal differentiation, as previously described (17,43). For sensory neuron differentiation (46), iPSCs were cultured to 60%-70% confluence, dissociated with accutase for 5 minutes, pelleted at 250 g for 3 minutes, plated on Matrigel-coated plates at 26,000 cells/ cm 2 , and cultured in E8 medium with 5 μM ROCK inhibitor for 24 hours. Differentiation medium DMEM-F12 containing 10% KnockOut Serum Replacement (Thermo Fisher Scientific), 0.3 μM LDN-193189 (Cellagen Technology), 2 μM A83-01 (Cellagen Technology), 6 μM CHIR99021 (STEMCELL Technologies), 2 μM RO4929097 (Cellagen Technology), 3 μM SU5402 (Tocris), and 0.3 μM retinoic acid (MilliporeSigma) (46) was changed every second day.…”
Section: Ipsc Differentiation Into Neurons and Sensory Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cell therapies involving cartilage regeneration and several current 3D bioprinting processes involve the use of synthetic and natural biological molecules such as growth factors to improve their proliferation and differentiation [9][10][11]. There is an ongoing search in the science community for alternatives of these growth factors and the existing synthetic materials, due to reports on their numerous negative effects and complete failure in cartilage regeneration [3,[12][13][14]. Several medicinal plant extracts have been suggested to stimulate adult stem cell proliferation and thus regeneration of damaged or diseased tissues.…”
Section: Introductionmentioning
confidence: 99%
“…As our ability to promote skeletal muscle differentiation and maturation from hiPSC sources improves [Chal et al, 2015[Chal et al, , 2016Xi et al, 2017], we can expect further advances in modeling of neuromuscular development, function, and breakdown to occur. Production of hiPSC-derived Schwann cells has been published [Liu et al, 2012;Cai et al, 2017], but their capacity to myelinate human neurons has yet to be reported within in vitro cocultures, highlighting the difficulty in producing such responses in human systems and an important avenue for future study. Innervation of cardiac muscle with sympathetic neurons has been reported and the capacity for neuronal activation to regulate spontaneous beat behavior in hiPSC-derived cardiomyocytes has been demonstrated [Oh et al, 2016].…”
Section: Complexitymentioning
confidence: 99%